Surfaces of gymnastic equipment as reservoirs of microbial pathogens with potential for transmission of bacterial infection and antimicrobial resistance - Zhang, Mengge; Ma, Yanan; Xu, Hai; Wang, Mingyu; Li, Ling (Frontiers in Microbiology, 2023)
Gymnastic equipment surfaces are shared by many people, and could mediate the transfer of bacterial pathogens. To better understand this detrimental potential, investigations on the reservoirs of bacterial pathogens and antimicrobial resistance on the surfaces of gymnastic equipment were performed by analyzing the bacterial community structures, prevalence of viable bacteria, and presence of antimicrobial resistance on both indoor and outdoor gymnastic facilities. The results of high-throughput 16S rDNA amplicon sequencing showed that Gram-positive bacteria on the surfaces of indoor gymnastic equipment significantly enriched, including the opportunistic pathogen Staphylococcus strains, while Enterobacteriaceae significantly enriched on surfaces of outdoor gymnastic equipment. The analysis of α-diversities showed a higher richness and diversity for bacterial communities on the surfaces of gymnastic equipment than the environment. Analysis of β-diversities showed that the bacterial communities on the surfaces of gymnastic equipment differ significantly from environmental bacterial communities, while the bacterial communities on indoor and outdoor equipment are also significantly different. Thirty-four bacterial isolates were obtained from the surfaces of gymnastic equipment, including three multidrug Staphylococcus and one multidrug resistant Pantoea. In particular, Staphylococcus hemolyticus 5-6, isolated from the dumbbell surface, is a multidrug resistant, hemolytic, high- risk pathogen. The results of quantitative PCR targeting antibiotic resistance related genes (intI1, sul1 and blaTEM) showed that the abundances of sul1 and blaTEM genes on the surfaces of gymnastic equipment are higher than the environment, while the abundances of sul1 gene on indoor equipment are higher than outdoor equipment. These results lead to the conclusion that the surfaces of gymnastic equipment are potential dissemination pathways for highly dangerous pathogens as well as antimicrobial resistance, and the risks of indoor equipment are higher than outdoor equipment.